Introduction - Leung, Linda (Refuge: Canada’s Journal on Refugees, 2013)
The Special Focus section of this issue of Refuge is being edited by an “outsider” to Refugee Studies. By that I mean that my professional life has not focused on investigating refugee issues per se, but instead has been concerned with how technology is accessed and deployed by groups and communities. Therefore, what this Special Focus section off ers are some different perspectives on technology’s role in the refugee experience through the lenses of various disciplines that actually study technology adoption and uses. In doing this, I am hoping to begin an interdisciplinary dialogue between Refugee Studies and Technology Studies scholars about policies, models, and politics of technology provision, access and use with specific reference to refugee service provision in situations of displacement. To this end, I have also included contributions from other “outsiders” to encourage the sharing of data and knowledge across sectors.